Brigatinib in ALK-positive non-small cell lung cancer: real-world data in the Latin American population (Bri-world extend CLICaP) (2021)
Background: Brigatinib has demonstrated its efficacy as first-line therapy and in further lines for ALK-positive non-small cell lung cancer (NSCLC) patients; however, real-world data in Latin America are scarce. Methods: From January 2018 to March 2020, 46 patients with advanced ALK-positive NSCLC received brigatinib as second or further line of therapy in Mexico and Colombia. The primary end point was progression-free survival (PFS); secondary end point was time to treatment discontinuation (TTD). Results: At a median follow-up of 9.3 months, the median PFS was 15.2 months (95% CI: 11.6-18.8), and TTD was 18.46 months (95% CI: 9.54-27.38). The estimated overall survival at 12 months was 80%. Safety profile was consistent with previously published data. Conclusion: Brigatinib is an effective treatment for previously treated ALK-positive NSCLC patients in a real-world setting.